2020
DOI: 10.1177/1087724x19899100
|View full text |Cite
|
Sign up to set email alerts
|

Using PPP to Procure Social Infrastructure: Lessons From 20 Years of Experience in Ireland

Abstract: Ireland has almost two decades of experience with using public private partnerships (PPPs) for the procurement of social infrastructure such as schools, courthouses, and health facilities. This article focuses on Ireland’s schools sector where 27 school buildings with an estimated capital value of €500 million have been procured via PPP to date. We review the changes that have occurred to the governance of PPPs and supporting institutional structures, which have evolved considerably over the past 20 years. Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
(14 reference statements)
1
15
0
Order By: Relevance
“…We recognize comparable cases have been documented in the literature highlighting lessons of location specific institutional evolution (see for example: Chan, 2020; Biygautane, 2022; Biygautane et al. , 2019; Chan, 2020; Malpass, 2011; Reeves, 2015; O'Shea et al. , 2020).…”
Section: Discussion and Conclusion: Achievements Lessons Challenges A...supporting
confidence: 65%
“…We recognize comparable cases have been documented in the literature highlighting lessons of location specific institutional evolution (see for example: Chan, 2020; Biygautane, 2022; Biygautane et al. , 2019; Chan, 2020; Malpass, 2011; Reeves, 2015; O'Shea et al. , 2020).…”
Section: Discussion and Conclusion: Achievements Lessons Challenges A...supporting
confidence: 65%
“…Over the last two decades, 24 projects of total capital value of over €5 billion have been implemented [4]. O'Shea and coauthors state that the Ministry of Public Expenditure and Reform in the Review of the Capital Plan 2016-2021 identified three phases in the development of PPPs in Ireland [40]: (1) the first phase of the PPP development was focused on travel infrastructure and primary education, (2) the second phase of development was concerning social housing, (3) while the third included projects regarding higher education, health, and courts.…”
Section: Review Of Previous Research In This Areamentioning
confidence: 99%
“…Public-Private Partnership (PPP) mechanisms, involving cross-sector collaboration, have become an increasingly important tool of government action to deliver social infrastructure including urban and rural regeneration schemes. International experience with PPP approaches has been mixed regarding the governance of PPP procurement including issues in relation to ex-ante and ex-post evaluation of Value For Money (VFM) and risk transfer [31,32]. The European PPP Expertise Centre (EPEC) suggests that the successful use of the PPP mechanism depends on conducive legal regulatory and institutional framework and processes [33,34].…”
Section: Public-private Partnerships Structuresmentioning
confidence: 99%